STUDI PRAKTIK INVESTOR RELATIONS PADA BADAN PENANAMAN MODAL DAN PERIZINAN TERPADU (BPMPT) KOTA SURAKARTA - , FIRDHA IRMAWANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Investor Relations is used to describe a part of an corporate communication that aims to attract investor. Badan Penanaman Modal dan Perizinan Terpadu Kota Surakarta (Investment and Integrated Licensing Board of Surakarta City) is appointed by local government to implement the investment policies and services by promoting the potential investment in Surakarta City. The study describes the Investor Relations practices on Badan Penanaman Modal dan Perizinan Terpadu Kota Surakarta (Investment and Integrated Licensing Board of Surakarta City). Investor Relations practices in a corporation is used as a model to describe the Investor Relations practices in a local government. The result shows that Badan Penanaman Modal dan Perizinan Terpadu Kota Surakarta (Investment and Integrated Licensing Board of Surakarta City) has not fully adopted the Investor Relations practices. The efforts to promote the region as marketing activities to attract investors has been done, but Badan Penanaman Modal dan Perizinan Terpadu Kota Surakarta (Investment and Integrated Licensing Board of Surakarta City) overlook the importance of investor mapping to address the need of different investors. The role of media as an intermediary to indirectly communicate with the investors also escaped the attention from Badan Penanaman Modal dan Perizinan Terpadu Kota Surakarta (Investment and Integrated Licensing Board of Surakarta City)